Self-Efficacy in the Prediction of GPA and Academic Computer Use in Undergraduate Translation Students at a Saudi University - Brashi, Abbas (Frontiers in Psychology, 2022)
Since the beginning of the Covid-19 pandemic, academic institutions have faced the challenge of understanding the social-psychological features that produce better academic performance among translation students in an online learning environment. Although self-efficacy is widely studied in a variety of teaching and learning models, few studies have examined self-efficacy in regard to translation students. This empirical study aims to examine the roles of general self-efficacy and computer self-efficacy in terms of the academic achievement and computer use of translation students during the Covid-19 pandemic. The participants included 83 undergraduate translation students at the English Language Department of Umm Al-Qura University, Saudi Arabia. They completed the General Self-Efficacy Scale and Computer Self-Efficacy Scale questionnaires. The results found self-efficacy scores were a significant predictor of overall GPA scores, highly predictive of computer self-efficacy, and also predicted an increased typing frequency and computer usage. This study suggests that translation students with greater levels of self-efficacy will be more likely to possess social-psychological features that align with the independent, self-directed nature of online learning environments.